2022
DOI: 10.3389/fnhum.2021.752138
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Language-and-Memory Networks in Patients With Temporal Lobe Epilepsy by Using the GE2REC Protocol

Abstract: Preoperative mapping of language and declarative memory functions in temporal lobe epilepsy (TLE) patients is essential since they frequently encounter deterioration of these functions and show variable degrees of cerebral reorganization. Due to growing evidence on language and declarative memory interdependence at a neural and neuropsychological level, we propose the GE2REC protocol for interactive language-and-memory network (LMN) mapping. GE2REC consists of three inter-related tasks, sentence generation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 153 publications
(248 reference statements)
0
3
1
Order By: Relevance
“…In the picture retrieval task, the hyperconnectivity, especially in right TLE patients, originated from the LANG in the prefrontal cortex and extended from this region to the other areas. While other investigators have also reported the intervention of prefrontal areas in the memory network, 15,16,36,37 our results showed that this effect is initiated from the left hemispheric areas to the other intracranial regions. Also, our finding suggests an ipsilateral hypoconnectivity in PHIP.…”
Section: Altered Functional Connectivity In the Memory Networkcontrasting
confidence: 48%
See 3 more Smart Citations
“…In the picture retrieval task, the hyperconnectivity, especially in right TLE patients, originated from the LANG in the prefrontal cortex and extended from this region to the other areas. While other investigators have also reported the intervention of prefrontal areas in the memory network, 15,16,36,37 our results showed that this effect is initiated from the left hemispheric areas to the other intracranial regions. Also, our finding suggests an ipsilateral hypoconnectivity in PHIP.…”
Section: Altered Functional Connectivity In the Memory Networkcontrasting
confidence: 48%
“…Effective connectivity can be measured by fMRI and dynamic causal modeling (DCM) as one of the most common methods for calculating and modeling the effective neural communication between brain regions and networks. 12,13 Several studies have examined the effect of TLE on the performance of memory and language networks using fMRI [14][15][16] including encoding and retrieval of abstract images, visual scenes, faces, words, object location, and spatial navigation tasks. 14,15,[17][18][19] Several investigations have also used the DCM method to map the memory or language networks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations